2014
DOI: 10.1002/jnr.23436
|View full text |Cite
|
Sign up to set email alerts
|

Projection target‐specific action of nicotine in the caudal nucleus of the solitary tract

Abstract: The brainstem nucleus of the solitary tract (NTS) is the key integrating relay in the central processing of sensory information from the thoracic and from most subdiaphragmatic viscera. Modulation of neuronal excitability and synaptic activity in the NTS by nicotinic agents can have potent effects on vital physiological functions, such as feeding, digestion, respiration, and blood circulation. Caudal NTS neurons demonstrate considerable heterogeneity in projection targets, synaptic properties, and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
(113 reference statements)
2
3
0
Order By: Relevance
“…These studies demonstrated that in the cNTS nicotine application can activate cNTS neurons either by increasing glutamatergic synaptic release, or by direct somatodendritic activation. In addition, it seems that depending on the cNTS projection area of the brain, the responsiveness to nicotine is pre-or post-synaptically mediated (Feng et al, 2012;Feng and Uteshev, 2014). Thus, the present and previous studies (Feng et al, 2012;Feng and Uteshev, 2014;Kalappa et al, 2011), reiterate the role of nicotinic receptors in the cNTS in mediating the effects of ACh in the cNTS.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These studies demonstrated that in the cNTS nicotine application can activate cNTS neurons either by increasing glutamatergic synaptic release, or by direct somatodendritic activation. In addition, it seems that depending on the cNTS projection area of the brain, the responsiveness to nicotine is pre-or post-synaptically mediated (Feng et al, 2012;Feng and Uteshev, 2014). Thus, the present and previous studies (Feng et al, 2012;Feng and Uteshev, 2014;Kalappa et al, 2011), reiterate the role of nicotinic receptors in the cNTS in mediating the effects of ACh in the cNTS.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, it seems that depending on the cNTS projection area of the brain, the responsiveness to nicotine is pre-or post-synaptically mediated (Feng et al, 2012;Feng and Uteshev, 2014). Thus, the present and previous studies (Feng et al, 2012;Feng and Uteshev, 2014;Kalappa et al, 2011), reiterate the role of nicotinic receptors in the cNTS in mediating the effects of ACh in the cNTS. The present study does not however clarify whether such effects are a consequence of presynaptic of somatodendritic actions of ACh.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nicotine increases vagal afferent discharge and increases the probability of glutamate release from afferent terminals within the NTS (48). It also induces a postsynaptic current in a subpopulation of NTS neurons (27,28,48,96). Nicotine has been shown to activate GABAergic NTS neurons (101), however, the other phenotypes of NTS neurons activated by nicotine are not known.…”
Section: Introductionmentioning
confidence: 99%
“…The ST relays information to the NTS from sensory receptors of the visceral organs and other tissues [4,5,6,7,8,9]. The NTS is a highly heterogeneous population of neurons, where seemingly indistinguishable neighboring neurons could participate in very different autonomic (e.g., gastrointestinal and cardiorespiratory reflexes) and nociceptive functions [8,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%